Fosterage in Crimea (based on the anonymous manuscript kept at the Institute of Oriental Manuscripts, RAS) - Kozintcev M.A. (Золотоордынское обозрение)
Research objectives: This article considers some features of fosterage as a social institution that existed in the Crimean Khanate throughout most of its history. Above all, the ceremonial and practical aspects associated with the transfer of the children to the caregiver, the process of their education and return to their family are considered. Research materials: A section of the anonymous manuscript “History of Crimea” kept at the collection of the Institute of Oriental Manuscripts, RAS, under shelf mark B 747. Results and novelty of the research: Being widely practiced by many peoples of the Caucasus, fosterage had spread to the territory of the Crimean Khanate. Understanding of the origins and essence of this method of child rearing was greatly augmented by the works of famous Soviet ethnographer and historian, M.O. Kosven (1885–1967), which were dedicated to the institution of the family and social structure of the mountain peoples, especially his article “Fosterage”. Meanwhile, the Crimean material is only briefly mentioned in that article. The text of one of the sections of the anonymous manuscript, “History of Crimea”, shows that by the second half of the eighteenth century, fosterage had been practiced in Crimea only by representatives of the most privileged part of society, primarily by members of the ruling Giray dynasty. As might be assumed, the preservation of this institution was mainly dictated by political considerations, while its practical expediency for raising a child was no longer obvious. However, children of the Crimean khans continued to be sent to the Caucasian families for upbringing. The process of giving the children to the caregiver (atalık) and taking them back was subject to consistently followed protocols defining behavior of all participants of the process. Final institutionalization of fosterage was associated with the official recognition of caregivers among the highest court officials of the Crimean Khanate. This article provides the full text of the aforementioned section of “History of Crimea” in Ottoman Turkish, transcribed and translated into Russian.